Synergistic effects of imatinib and carboplatin on VEGF, PDGF and PDGF-Rα/ß expression in squamous cell carcinoma of the head and neck in vitro - Schultz, Johannes D.; Rotunno, Sarah Elena; Riedel, Frank; Anders, Clemens Frithjof; Erben, Philipp; Hofheinz, Ralf-Dieter; Lammert, Anne; Thorn, Carsten Volker; Sommer, Ulrich; Hörmann, Karl; Sauter, Alexander (International journal of oncology, 2011)
Head and neck squamous cell carcinoma (HNSCC) is an aggressive epithelial malignancy. The development of new treatment modalities in order to improve long-term survival of patients with HNSCC is imperative. Numerous studies have demonstrated that carcinogenesis and tumor cell dissemination is influenced by the tumor microenvironment. The protein-kinase-receptors (PTKs) are essential elements of the intracellular signal transduction pathway and regulate cell growth, development and apoptosis. Cell proliferation, migration, induction of tumor vascularization and carcinogenesis, invasion is regulated by a variety of angiogenic factors, such as PDGF (platelet-derived growth factor), VEGF (vascular endothelial growth factor) and their respective tyrosine kinase receptors (PDGF-R and VEGF-R). They present promising targets for anti-cancer therapy through abrogation of impaired signaling pathways. Indeed, imatinib, a small molecule drug targeting these protein kinases, has antiproliferative effects in several cancer types. The purpose of this study was to investigate the potential synergism of imatinib and carboplatin on the expression of PDGF, PDGF-R α/ß and VEGF in different HNSCC cell lines. Several tumor cell lines were subjected to increasing concentrations of carboplatin (3 and 7.5 µmol/l) and imatinib (18 and 30 µmol/l) and ELISA, immunohistochemical methods and RQ-PRC after 48, 72, 120 and 240 h were used to assess their expression levels. While PDGF-Rα/ß expression was unimpaired at lower imatinib concentrations (18 µmol/l), PDGF-Rα/ß expression was suppressed at 30 µmol/l, and suppression was enhanced by the presence of carboplatin. By RQ-PCR, a significant reduction of PDGF-Rα/ß expression was detected (p<0.5). We observed explicit significant reduction in VEGF levels with increasing concentrations of imatinib and with the combination of the two chemotherapeutic drugs (p<0.5). We report for the first time evidence of synergism of imatinib and carboplatin in suppressing VEGF, PDGF and PDGF-Rα/ß expression in HNSCC.